Pengaruh Marketing Mix Dan Brand Image Terhadap Peningkatan Penjualan Produk Dalam Mempertahankan Eksistensi Tenun Ikat Medali Emas Kota Kediri - Aditya Bagus Pratama; Sonny SM Laksono (Otonomi, 2023)
The research in this thesis is motivated by the conditions of MSMEs which are getting tighter from time to time, so that every MSME must create a new marketing strategy in order to maintain and gain a large market share. Problem formulation from theses are: 1) Does the marketing mix have a direct effect on increasing sales of Bandar Ikat Weaving SMEs in Kediri City? 2)Does brand image have a significant effect on the existence of Bandar Ikat Weaving SMEs in Kediri City? The method of data collection was carried out through a questionnaire which distributed to gold medal ikat customers who have made more than two purchases. The sample taken is 55 respondents, the data obtained are then processed using tools IBM SPSS 21 and analysis using multiple linear regression analysis. This analysis includes validity and reliability tests, correlation analysis, testing The hypothesis includes classical assumption test, t test, F test and coefficient of determination. Based on the results of the study, it can be concluded: 1) Based on the t test The marketing mix has a positive and significant effect on increasing sales of MSMEs Weaving Gold Medals. This indicates that the better the marketing mix carried out by MSMEs will further increase Sales Increase. 2) Based on test t Brand image has a positive and significant effect on increasing sales. This indicates that the better the level of brand image owned, it does not improve student decisions using benefit . 3) Based on test F Marketing mix and brand image together have an effect on Increased sales of gold medal ikat weaving. So that the weaving of the Mas medal can maintain its existence.